Giải và biện luận theo tham số m m(x-m+3)=m(x-2)+6 Giúp e vs

Question

Giải và biện luận theo tham số m
m(x-m+3)=m(x-2)+6
Giúp e vs

in progress 0
Ruby 4 phút 2021-09-10T12:48:34+00:00 1 Answers 0 views 0

Answers ( )

    0
    2021-09-10T12:50:21+00:00

    Đáp án:

    \(\begin{array}{l}
    Voi\,\,m = 2;\,\,m = 3 \Rightarrow Pt\,co\,\,vo\,\,so\,\,nghiem\\
    Voi\,\,m \ne 2,\,\,m \ne 3 \Rightarrow Pt\,\,vo\,\,nghiem.
    \end{array}\)

    Giải thích các bước giải:

    \(\begin{array}{l}
    \,\,\,\,\,m\left( {x – m + 3} \right) = m\left( {x – 2} \right) + 6\\
    \Leftrightarrow mx – {m^2} + 3m = mx – 2m + 6\\
    \Leftrightarrow – {m^2} + 3m = – 2m + 6\\
    \Leftrightarrow – {m^2} + 5m – 6 = 0\\
    \Leftrightarrow \left[ \begin{array}{l}
    m = 2\\
    m = 3
    \end{array} \right.\\
    Voi\,\,m = 2;\,\,m = 3 \Rightarrow Pt\,co\,\,vo\,\,so\,\,nghiem\\
    Voi\,\,m \ne 2,\,\,m \ne 3 \Rightarrow Pt\,\,vo\,\,nghiem.
    \end{array}\)

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )